Prehypertension in the Krasnoyarsk Region: prevalence, correlation with sociodemographic and cardiometabolic risk factors - Yu. I. Grinshteyn; V. V. Shabalin; R. R. Ruf; A. Yu. Shtrikh; Yu. A. Balanova (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To evaluate the prevalence of prehypertension and its interrelations with other cardiovascular risk factors in Krasnoyarsk Region population.Material and methods. The present study, conducted in the framework of epidemiological research ESSE-RF, included 1603 people (age 25-64 years) of urban and rural population of the Krasnoyarsk Region. All participants underwent the questionnaire test, office blood pressure measurement, anthropometry, and biochemical blood analysis. Persons with 120-139/80-89 mm Hg blood pressure was subsumed to the prehypertension group. Statistical processing of the results was performed in IBM SPSS v. 22. Differences in prehypertension prevalence were assessed for statistical significance using the Pearson’s chi-squared test. The influence of sociodemographic factors and laboratory parameters was evaluated using logistic regression with the gradual elimination of insignificant factors. Statistical significance was taken into account at p<0,05.Results. We determined that 29,1% of Krasnoyarsk Region population had prehypertension. It was more prevalent in males compared to females (32,5% vs 27,2% respectively), in younger people compared to older (41,6% in 25-34 vs 16,5% in 55-64), and in urban population compared to rural (30,7% vs 24,7% respectively). Prehypertension prevalence in the Krasnoyarsk Region was lower compared with the average country statistics (35,0%) due to the greater prevalence of arterial hypertension. The significant predictors of prehypertension were higher education, obesity and hypertriglyceridemia.Conclusion. The prevalence of prehypertension in Krasnoyarsk Region was 29,1%; it is lower than the average data over Russia because of a higher percentage of people with arterial hypertension and a lower percentage of optimal blood pressure in Krasnoyarsk Region population. The percentage of prehypertension decreased with age. Higher education, obesity and hypertriglyceridemia increased the risk of prehypertension.